An Analysis of the Effectiveness of the Course Review Horay Learning Model in Enhancing Students’ Interest in Islamic Religious Education - Rafiki, Niken Aufa; Sada, Heru Juabdin; Yusnita, Erni (Universitas Muhammadiyah Mataram, 2026)
This study is motivated by the low level of students’ interest and engagement in Islamic Religious Education and Character Education (PAI and Budi Pekerti), indicating the need for a more innovative, interactive, and enjoyable learning model. The objective of this study is to examine the effectiveness of the Course Review Horay (CRH) learning model in enhancing students’ learning interest in PAI and Budi Pekerti at SMK Muhammadiyah Way Sulan. This study employs a quantitative experimental method using a posttest-only control group design. The sample was selected through simple random sampling and divided into an experimental group (treated with the CRH model) and a control group (taught using conventional methods). The research instrument consisted of a learning interest questionnaire that had been tested for validity and reliability, yielding a reliability coefficient of 0.812, indicating high internal consistency. The data were analyzed using an independent samples t-test to determine the significance of differences between the two groups. The findings reveal that the CRH learning model has a positive and statistically significant effect on students’ learning interest, as reflected in increased participation, improved classroom interaction, and higher levels of enthusiasm compared to conventional teaching methods. The novelty of this study lies in the implementation of the CRH model within Islamic Religious Education at the vocational high school level, a context that remains underexplored in prior research, thereby contributing to the advancement of cooperative learning models in religious education.